In situ electrosynthesis of hydrogen peroxide with an improved gas diffusion cathode by rolling carbon black and PTFE1. Issue 80 (2nd September 2015) - Luo, Haijian; Li, Chaolin; Wu, Chiqing; Dong, Xiaoqing
<x xml:space="preserve">Abstract</x> A simply structured gas diffusion electrode (GDE) was constructed by rolling carbon black and PTFE as a conductive catalyst layer to enhance the producibility of hydrogen peroxide.